(untitled) (Revista Investigación & praxis en CS Sociales, 2025)
The research aimed to strengthen the identity values of Afro-descendants through traditional Afro dance, using Ausubel’s meaningful learning. This study was conducted with 25 third-grade students at the Rural Educational Institution Ana Joaquina Rodríguez de Cañaverales, in San Juan del Cesar, Guajira. A qualitative approach and an action research design were employed. Data collection instruments such as the written test, field diary, and estimation scale were applied. The results showed that the students identified the meaning of symbols and words, connecting new concepts with their previous knowledge. They also integrated cultural principles and values of Afro identity, incorporated meanings about Afro-Colombian history, practiced dance movements, and demonstrated deep respect for Afro cultural contributions. The conclusions confirmed the relevance of using strategies based on meaningful learning, as the students’ cultural identity was strengthened.